Should post-Keynesians make a behavioural turn? - John E. King (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2013)
This paper deals with the relationship between post-Keynesian and behavioural economics. I begin by responding critically to Paul Davidson's claim that Keynes was the first behavioural economist. Then I discuss some recent work in behavioural macroeconomics, which reveals some important strengths but also some fundamental weaknesses. Next I outline what (Old) behavioural economists have had to say about macroeconomics, beginning with the father of the school, Herbert Simon, and considering the contributions of some of his disciples. I then reverse the question and ask what post-Keynesians have had to say about behavioural economics, Old and New. I conclude by identifying some potential sources of difficulty and also suggesting some areas of macroeconomics where cooperation between post-Keynesians and behavioural economists seems especially promising.
Keywords: B22; B5; E12; 330; behavioural economics; macroeconomics; post-Keynesian economics